Materi Modul Projek Kurikulum Merdeka PAUD Berbasis Budaya Kearifan Lokal Melalui Pengenalan Alat Musik Gong Gumbeng Ponorogo - Fifi Ari Santi; Betty Yulia Wulansari; Muhammad ‘Azam Muttaqin (Jurnal Kajian Anak (J-Sanak), 2023)
The independent PAUD curriculum has been implemented since 2020 and is used to introduce material for the Strengthening Pancasila Student Profile Project. There are 2 scopes of the Merdeka Curriculum, namely Teaching Modules and Project Modules. This curriculum is used in accordance with the local wisdom context of each region, especially in Ponorogo and the implementation of this project module aims to analyze the material of the Merdeka PAUD Curriculum project module based on local wisdom culture through the introduction of the Ponoragan Gong Gumbeng musical instrument. The research method used is through a qualitative approach. descriptive. From the results of the analysis, the researchers found material for the Ponorogo Gong Gumbeng Project Module which included: (1) outing class to see a performance in Wringinanom village, (2) STEAM activity where we carried out painting gong gumbeng art tools from bamboo, (3) a book with a series of pictures of related activities with gong gumbeng, (4) exhibition of exhibition works related to gong gumbeng performances at schools.